The hall monitors are fired! - Chabert, Jack; Loveridge, Matt (New York, NY : Scholastic Inc., 2018)
Sam Graves and his friends Lucy and Antonio have used their positions as hall monitors to thwart Orson Eerie's attacks on the students of Eerie Elementary--but now Orson is determined to get them fired before his next attack, planned for the annual Kickball Showdown.
2.9
K-3
500L
Keywords: Haunted schools -- Juvenile fiction; Elementary schools -- Juvenile fiction; Kickball -- Juvenile fiction; Best friends -- Juvenile fiction; Haunted places -- Fiction; Elementary schools -- Fiction; Kickball -- Fiction; Best friends -- Fiction; Friendship -- Fiction; Horror fiction